Facile Synthesis and High Capacitive Performance of 3D Hierarchical Ni(OH)2 Microspheres. (1st April 2016) - Du, Hongmei; Wang, Yijing; Yuan, Huatang; Jiao, Lifang
Abstract: Ni(OH)2 microspheres composed of intersected nanopetals are hydrothermally produced using NH4 F as the morphology directing agent. The amount of NH4 F can not only affect the morphology of Ni(OH)2, but also the microstructure and pore size. Through rational control of the NH4 F dosage, Ni(OH)2 microspheres with macro/mesoporous structure are obtained. The 3D hierarchical structure can not only increase the diffusion rate of electrolyte into the inner part of active materials, but also reduce the diffusion distance to the interior surface. The sample displays a maximum discharge specific capacity of 1280.9 F g −1 at 0.5 A g −1 and 655.2 F g −1 at 10 A g −1 in 2 M KOH. The capacity loss is only 2% after 700 cycles.